A Prediction Model of Tunnel Surrounding Rock Deformation Based on Induced Ordered Weighted Averaging Theory and its Application. Issue 4 (May 2019) - Fan, Fangfang; Jian, LI
Abstract: For the different prediction accuracy of tunnel surrounding rock deformation prediction model are different. Based on induced ordered weighted averaging theory(IOWA), IOWA modified combined forecasting model of tunnel surrounding rock deformation has been put forward with the relationship between the accuracy and the weight of a single prediction model. With the monitoring data of Mila Mountain tunnel of highways from Lasa to Linzhi, coupling the time series prediction model of deformation and exponential smoothing model of two kinds of single tunnel, IOWA modified combination prediction model for tunnel surrounding rock deformation has been built up. The result shows that predicted displacement of IOWA modified combination prediction model for tunnel surrounding rock deformation is closer to the measured value and has higher accuracy. The combined model for the prediction of tunnel surrounding rock deformation is feasible.